PEMBELAJARAN MENULIS KEMBALI ISI TEKS BIOGRAFI BERBASIS FILM DENGAN MENGGUNAKAN METODE CLUSTERING YANG BERFOKUS PADA PENGEMBANGAN GAGASAN KE DALAM TEKS DESKRIPTIF PADA PESERTA DIDIK KELAS X SMK TAMANSISWA BANDUNG TAHUN PELAJARAN 2020/2021 - Estiana; Any Budiarti; Adi Rustandi (STKIP Subang, 2022)
This research is motivated by the low ability of students in learning to write biographical texts. This study aims to determine the ability of planning and implementing the researcher's learning; students' writing skills; and the effectiveness of the clustering method in learning to rewrite the contents of a film-based biographical text that focuses on developing ideas into descriptive texts; The research method used is an experiment with a quasi-experimental design. The results of this study are: first, the ability of researchers to plan learning gets a score of 3.78 in the very good category, and the ability of researchers to carry out learning gets a score of 3.67 with a good category. Second, the ability of students has increased based on the Paired Samples Test which proves the value of Asymp. Signature. (2-tailed) of 0.000 is less than 0.05, then Ha2 is accepted. Third, an effective grouping method is applied in learning to rewrite the contents of a film-based biographical text that focuses on developing ideas into descriptive text based on the Independent Samples Test which proves the value of Asymp. Signature. (2-tailed) of 0.020 is smaller than 0.05, then Ha3 is accepted. Based on the results of the study, the researcher concluded that learning to rewrite the contents of a film-based biographical text using a grouping method that focused on developing ideas into descriptive texts for class X students of SMK Tamansiswa Bandung in 2020/2021 was successful.